2022
DOI: 10.23960/mtk/v10i1.pp70-82
|View full text |Cite
|
Sign up to set email alerts
|

Model Integrating Society, Science, Environment, Technology and Collaborative Mind Mapping Mempengaruhi Penalaran Matematis Dan Multiple Intellegences

Abstract: The reasoning is critical in all fields, but especially in mathematics. The purpose of this study is to ascertain the differences in students' mathematical reasoning abilities when they are exposed to learning that integrates society, science, the environment, technology, and collaborative mind mapping (ISSETCM2). This is a quasi-experiment with a population of 220 students and a sample size of 60 students. The sampling technique used is simple random sampling without replacement (without replacement). Mathema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Several studies related to the use of the ISSETCM2 learning model have been found, including that the learning model has a good effect on students' ability to relate elements of science, environment, technology, society, and culture using CM2, and that students can gain direct experience through scientific work on the impact of environmental pollution and mathematical reasoning (Mujib et al, 2022). Similarly, some of them stated that AQ affected selfefficacy (Suryadi & Santoso, 2017), problem-solving (Fauziah et al, 2020;Purnamasari et al, 2019), logical thinking (Ahmar et al, 2018), and learning achievement (Safi'i et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies related to the use of the ISSETCM2 learning model have been found, including that the learning model has a good effect on students' ability to relate elements of science, environment, technology, society, and culture using CM2, and that students can gain direct experience through scientific work on the impact of environmental pollution and mathematical reasoning (Mujib et al, 2022). Similarly, some of them stated that AQ affected selfefficacy (Suryadi & Santoso, 2017), problem-solving (Fauziah et al, 2020;Purnamasari et al, 2019), logical thinking (Ahmar et al, 2018), and learning achievement (Safi'i et al, 2021).…”
Section: Introductionmentioning
confidence: 99%